2016
DOI: 10.1002/ajhb.22843
|View full text |Cite
|
Sign up to set email alerts
|

Does allostatic load calculation method matter? Evaluation of different methods and individual biomarkers functioning by race/ethnicity and educational level

Abstract: These findings highlight the continued importance of studying the concept of "weathering" or allostatic load at the population level and need to better understand how population groups facing exclusion from economic, social, and political power may internalize this position which may cause early health deterioration and ultimate mortality chance through different expression of health insults and premature aging. Am. J. Hum. Biol. 28:627-635, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 67 publications
4
57
0
Order By: Relevance
“…Although the operational definitions of allostatic load vary across studies [28], the allostatic load metric is considered a robust estimator of multi-system dysregulation in population studies [30]. While it is valuable to examine allostatic load as a composite score, examining dysregulation within the individual allostatic load systems can help identify underlying pathways through which the allostatic load response is manifested, according to the population’s specific characteristics [30]. As such, we examined whether the chronic stress associated with weight discrimination impacts both allostatic load and seven individual systems used to define allostatic load to elucidate the underlying pathways through which weight discrimination promotes dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the operational definitions of allostatic load vary across studies [28], the allostatic load metric is considered a robust estimator of multi-system dysregulation in population studies [30]. While it is valuable to examine allostatic load as a composite score, examining dysregulation within the individual allostatic load systems can help identify underlying pathways through which the allostatic load response is manifested, according to the population’s specific characteristics [30]. As such, we examined whether the chronic stress associated with weight discrimination impacts both allostatic load and seven individual systems used to define allostatic load to elucidate the underlying pathways through which weight discrimination promotes dysregulation.…”
Section: Introductionmentioning
confidence: 99%
“…AL is conceptualized as a latent construct that is best represented using a number of measured, biological indicator variables that represent stress‐mediated systemic physiological dysregulation (Howard & Sparks, ). In past research, a key determinant for selection of indicators included in AL measures has been the availability of and logistical access to various biomarkers that are believed to represent the key body systems involved in development of AL.…”
Section: Selection Of Al Indicatorsmentioning
confidence: 99%
“…Differences in educational attainment may even influence which mediators directly reflect allostatic load development. Recently,Howard and Sparks (2016) reported that those with lower educational attainment had allostatic load scores primarily loading on both metabolic and immune biomarkers, while allostatic load primarily loaded on metabolic mediators only in those with higher educational attainment. SES influences how individuals interact with their cultures and environments, and such differences are reflected in variable assessments of allostatic load across social settings(McEwen & Seeman, 1999).…”
mentioning
confidence: 99%
“…Mediators contributing to allostatic load also may vary by ethnicity. For example, non-Hispanic "blacks" may have allostatic load scores primarily influenced by inflammatory processes whereas allostatic load in non-Hispanic "whites" may be driven mostly by metabolic mediators(Howard & Sparks, 2016).Allostatic load indices also are influenced by DNA variation. For example, telomere length is negatively associated with stressor exposure.…”
mentioning
confidence: 99%